Kobiety i mężczyźni jako uczestnicy rozwodowych mediacji rodzicielskich = Women and men as participants of parental divorce mediations - Lipowicz, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The subject of research presented in the article are the results of parental divorce mediations as perceived by women and men. The research covered 29 couples who participated in parental divorce mediations which resulted in compromise. The basis of the research was an uncategorized in-depth interview.
Keywords: mediacje rozwodowe; konflikt rodziców; równowaga sił; opieka rodzicielska; kobiety; mężczyźni; divorce mediations; parental conflict; balance of power; parental care; women; men